Impacted permanent incisors associated with compound odontoma - Machado, Cintia de Vasconcellos; Knop, Luégya Amorin Henriques [UNESP]; Rocha, Maria Celina Barreiros Siquara da; Telles, Paloma Dias da Silva (BMJ Publishing Group LTD, 2015)
Odontomas are the most common odontogenic tumours of the maxillary bones, characterised by a slow growth and benign behaviour. They are usually small, asymptomatic and diagnosed after routine radiographic examination. The aim of this study was to report a case of a compound odontoma in the anterior maxilla of a 7-year-old girl, which was causing the impaction of the maxillary right central and lateral incisors, as well as the prolonged retention of the corresponding primary teeth. We also aimed to review the literature about these tumours, since they are not part of the dentist's day-to-day clinical practice. The clinical and radiographic features, the diagnosis and treatment of the case were discussed in this work.